Cloning internet applications with Ruby: make your own TinyURL, Twitter, Flickr, or Facebook using Ruby - Sheong, Chang Sau (Community experience distilled, 2010)
Most users on the Internet have a few favorite Internet web applications that they use often and cannot do without. These popular applications often provide essential services that we need even while we don’t fully understand its features or how they work. Ruby empowers you to develop your own clones of such applications without much ordeal. Learning how these sites work and describing how they can be implemented enables you to move to the next step of customizing them and enabling your own version of these services. This book shows the reader how to clone some of the Internet's most popular applications in Ruby by first identifying their main features, and then showing example Ruby code to replicate this functionality. While we understand that it connects us to our friends and people we want to meet up with, what is the common feature of a social network that makes it a social network? And how do these features work? This book is the answer to all these questions. It will provide a step-by-step explanation on how the application is designed and coded, and then how it is deployed to the Heroku cloud platform. This book’s main purpose is to break up popular Internet services such as TinyURL, Twitter, Flickr, and Facebook to understand what makes it tick. Then using Ruby, the book describes how a minimal set of features for these sites can be modeled, built, and deployed on the Internet.